PERAN SUMBER DAYA MANUSIA (SDM) UNTUK MENINGKATKAN EFISIENSI OPERASIONAL PT. MAJU JAYA PAITON DALAM PENGIRIMAN LIMBAH B3 - Muftihatul Khaira; Dila Rahmawati; Riza Nur Aini; Rica Rachmawati; Tri Indah Wahyuni; Istiana Kudsi Falqi Taggyah; Nadia Muthiah Zuhri; Uswatun Hasanah; Nuril Masruroh (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2025)
This study aims to examine in depth the role of human resources (HR) in improving the operational efficiency of PT Maju Jaya Paiton, especially in hazardous and toxic waste (B3) shipping activities. This research uses a descriptive qualitative approach, with data collection through in-depth interviews, direct observation, and documentation studies of SOPs, efficiency reports, and HR training data. Research informants included operational employees, logistics, HRD manager, and environmental manager. Analysis was conducted using thematic techniques and validated through triangulation of sources, techniques and time. The results showed that work competence, individual discipline, effective team communication, awareness of regulations, and a sense of responsibility for the environment are the main factors that determine operational efficiency. Structured training and certification, the implementation of a KPI-based evaluation system, the use of GPS tracking technology and electronic manifests (Festronic), as well as a work culture that emphasizes safety and compliance are proven to strengthen the role of HR in ensuring the smooth delivery of B3 waste. The conclusion of this study is that the success of hazardous waste transportation operations is strongly influenced by the quality and integration of HR functions, as well as system support and continuous supervision from both internal and external companies